Revolutionizing Management Accounting: The Role of Artificial Intelligence in Predictive Analytics, Automated Reporting, and Decision-Making - Milos Pavlovic; Cedomir Gligoric; Filip Zdravkovic; Danijela Pavlovic (Business & Management Compass, 2024)
Background and Aim: This study investigates the transformative impact of artificial intelligence (AI) on traditional management accounting practices, focusing on predictive analytics, automated reporting, and decision-making processes. The aim is to investigate how AI enhances the efficiency and accuracy of management accounting, as well as its strategic capabilities. Scope: The research is limited to AI applications within management accounting, examining current practices and the extent of AI integration. Methods: A mixed-methods approach combines an analysis of literature with available case studies. Results: The findings reveal that AI greatly enhances predictive analytics by boosting model accuracy and swiftly processing large datasets. AI-powered automated reporting improves efficiency and minimizes errors, while AI-based decision support systems deliver real-time insights and detect complex patterns, resulting in more effective strategic decisions. The study concludes that AI has the potential to revolutionize management accounting by enhancing predictive accuracy, operational efficiency, and strategic decision-making. However, successful implementation must address challenges related to data quality, system integration, and regulatory compliance. Originality: This paper contributes novel insights into how AI technologies can effectively integrate into accounting practices. Practical Implications: The findings are helpful for accounting professionals and business managers seeking to leverage AI to enhance their accounting practices, providing valuable recommendations for implementation and addressing potential challenges.